Exploring enzyme inhibition profiles of novel halogenated chalcone derivatives on some metabolic enzymes: Synthesis, characterization and molecular modeling studies. (October 2022) - Anil, Derya Aktas; Polat, M. Fatih; Saglamtas, Ruya; Tarikogullari, Ayse H.; Alagoz, M. Abdullah; Gulcin, Ilhami; Algul, Oztekin; Burmaoglu, Serdar
Abstract: Enzyme inhibition is a very active area of research in drug design and development. Chalcone derivatives have a broad enzyme inhibitory activity and function as potential molecules in the development of new drugs. In this study, the synthesized novel halogenated chalcones with bromobenzyl and methoxyphenyl moieties were evaluated toward the acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzymes and human erythrocyte carbonic anhydrase I (hCA I), and II (hCA II) isoenzymes. They showed highly potent inhibition ability toward AChE with Ki values of 1.83 ± 0.21–11.19 ± 0.96 nM and BChE with Ki values of 3.35 ± 0.91–26.70 ± 4.26 nM; hCA I with Ki values of 29.41 ± 3.14–57.63 ± 4.95 nM, and hCA II with Ki values of 24.00 ± 5.39–54.74 ± 1.65 nM. Among the tested enzyme inhibitions, compounds 14 and 13 were the most active compounds against AChE and BChE. Docking studies were performed to the most active compounds against AChE, BChE, hCA I and hCA II to propose a binding mode in the active site and molecular dynamics simulations were studied to check the molecular interactions and the stability of the ligands in the active site. The results may contribute to the development of new drugs particularly to treat some global disorders including Alzheimer's disease (AD), glaucoma, and diabetes. Graphical Abstract: ga1 Highlights: New halogenated chalcones were synthesized. Their structures were elucidated by IR NMR, and elemental analysis. Some halogenated chalcones displayed highly potent inhibition ability toward AChE, BChE, hCA I and II. Putative binding modes were proposed, and molecular dynamics simulations were performed.